PENERAPAN MODEL PEMBELAJAJARAN DENGAN TIPE CONTEXTUAL TEACHING AND LEARNING (CTL) DI SMA NEGERI 3 BUKITTINGGI - Abdul Istiqlal (Jurnal Akrab Juara, 2018)
This study aims to describe and know the application of learning model with Contextual Teaching and Learning type (CTL) in SMA Negeri 3 Bukittinggi. How this learning model can be useful and meaningful, both in the process of learning and in the daily life of students as learners. This research type is qualitative research by using descriptive method. The sample of this research is teacher and student of class XI IPS of SMA Negeri 3 Bukittinggi. The sample number of students is 30 people. The instrument of this study is the author's own and performance tests. This research data is analyzed by using deep appreciation of the phenomenon that occurs. The results of this study can be concluded that the application of learning methods using Contextual Teaching and Learning type (CTL) is very useful for teachers and students in improving the quality of teaching and learning process and learning outcomes of students or students. Keywords: Implementation, Context Teaching And Learning